Prevalence, Knowledge and Risk Factors for Postpartum Depression in Western Nepal - A Cross-Sectional Study - Karki, Sapana; Gurung, Shila (Europasian Journal of Medical Sciences, 2021)
Background: Postpartum depression(PPD)can be defined as nonpsychotic depression occurring within a year after childbirth, characterized by low mood, unusual thoughts, feeling of guilt, unexplained anxiety, worthlessness, and other depressive symptoms. Objective: This study aims to assess the prevalence, knowledge and risk factors of postpartum disorder. Methods: A cross-sectional descriptive study was conducted among 217 postpartum mothers in the outpatient department of psychiatry of a tertiary care hospital using the Edinburgh postnatal depression scale(EPDS). All the patients enrolled were directly interviewed using a structured questionnaire to identify the associated risk factors of postpartum depression. The data collected were checked for validity and analyzed using S.P.S. version 16.0. Results: Out of 217 patients, five women were found to have an EPDS (Edinburgh postnatal depression scale) score greater than 10. The prevalence of postpartum depression was found to be 2.3%. Upon evaluation of knowledge about postpartum depression, 90.3% of women were found to have a poor level of knowledge and 8.8% had a good knowledge level. The statistically significant factors associated with postpartum depression were the lack of support from family and partners (p<0.005). Conclusion: There was a comparatively low prevalence of P.P.D. in Western Nepal. Majority of the mothers (90.3%) were found not aware of P.P.D. The present study concluded on the need for educational intervention among the mothers regarding P.P.D. in Western Nepal.